Evaluation of a modification in ASTM C1609 standard for the study of synthetic fiber reinforced concrete under flexural load - Villalobos Ramírez, Francisco (2025)
The following study evaluated the viability of a modification in the procedure established in ASTM C1609 in order to lay evidence of the usefulness, or not, of the aforementioned standard in the testing of synthetic fiber reinforced concrete (SNFRC). Likewise, a comparison between the results obtained in flexural tests developed in accordance with EN14651 and those provided by the American statute was realized. A pseudoductil performance was found for SNFRC in which the addition of fibers allowed the concrete to resist loads even after its modulus of rupture was reached. Also, it was determined that a reduction in the loading rate established in ASTM C1609 allows for a higher probability of success for the test, especially when low fiber content is used. Furthermore, the speed reduction did not affect the results provided by the test. The European standard did not cause any inconvenience in the test execution, nevertheless, its results were not completely comparable to those obtained via de American normative.